2011
DOI: 10.4271/2011-01-0299
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Turbo Aftertreatment Position for Large Bore Diesel Engines - Compact & amp; Cost-Effective Aftertreatment with a Fuel Consumption Advantage

Abstract: Tier 4 emissions legislation is emerging as a clear precursor for widespread adoption of exhaust aftertreatment in offhighway applications. Large bore engine manufacturers are faced with the significant challenge of packaging a multitude of catalyst technologies in essentially the same design envelope as their pre-Tier 4 manifestations, while contending with the fuel consumption consequences of the increased back pressure, as well as the incremental cost and weight associated with the aftertreatment equipment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…As a further benefit, the pressure built-up from the turbocharger (typically up to 5 bar [10][11][12]) would lead to an increased residence time of the reactants at the catalyst, which would make a smaller total catalyst size possible as well as a decreased backpressure penalty [11,13]. This is also supported by numerical simulations by Subramaniam et al [13], who studied a preturbine placement of the entire aftertreatment system for a large bore diesel engine and predict a reduction of the catalyst volume > 40% and some decreased fuel consumption. Kröcher et al [11] reported that a pressure increase by a factor of two combined with half the catalyst size did not result in the same catalytic activity but a slightly lower one, probably due to diffusion limitations.…”
Section: Introductionmentioning
confidence: 99%
“…As a further benefit, the pressure built-up from the turbocharger (typically up to 5 bar [10][11][12]) would lead to an increased residence time of the reactants at the catalyst, which would make a smaller total catalyst size possible as well as a decreased backpressure penalty [11,13]. This is also supported by numerical simulations by Subramaniam et al [13], who studied a preturbine placement of the entire aftertreatment system for a large bore diesel engine and predict a reduction of the catalyst volume > 40% and some decreased fuel consumption. Kröcher et al [11] reported that a pressure increase by a factor of two combined with half the catalyst size did not result in the same catalytic activity but a slightly lower one, probably due to diffusion limitations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to temperatures of up to 180 • C higher at this location [18], the residence time is enhanced due to the higher pressure. These effects might enable a reduction of catalyst volume up to 40-70%, as shown in the case of diesel oxidations catalyst (DOC) and diesel particulate filter (DPF) applications [19,20]. However, at this location several challenges have to be faced.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the implementation of the gasoline particle filter (GPFs) has become an alternative to reduce the particles number emitted by those engines. However, the fact of incorporating more and more aftertreatment systems in the exhaust system causes an increase in the back pressure and, therefore, an increase in the pumping losses, producing increases in fuel consumption [14,15].…”
Section: Introductionmentioning
confidence: 99%